Accounting Students' Performance and Cognitive Complexity: Some Empirical Evidence. - Rosen, L. S.; Amernic, Joel H.; Beechy, Thomas H. (The Accounting Review, 1984)
ABSTRACT: Leaders in the accounting profession have cited the need for accountants to be able to function professionally in a complex and changing environment. The literature of cognitive development suggests that such individuals must possess a high level of cognitive complexity, and the literature on personality types shows that people self-select into professions partially as a result of their perceptions of the professional stereotype. Since the introductory and intermediate accounting courses may profoundly influence students' perceptions and their career choice, the courses should be designed so as to attract those more cognitively complex individuals whom the profession needs. This study analyzes the relative performance of introductory accounting students with high and low levels of cognitive complexity on structured versus unstructured course materials. Students at all levels of cognitive complexity performed equally well on highly structured accounting examination questions, but students with high levels of cognitive complexity performed significantly better on unstructured case materials. The implication of the results is that if accounting educators wish to attract students who can function in a complex and changing environment, the introductory accounting course should include unstructured course materials.